KEARIFAN TRADISI BUDAYA SEBAGAI SARANA PELESTARAIAN LINGKUNGAN SERTA POTENSI EKOWISATA PADA KOMUNITAS MASYARAKAT DI SEKITAR HUTAN LINDUNG PETUNGKRIYONO (STUDI KASUS NYADRAN GEBYOG) - Halim Ahmad; Tri Retnaningsih Soeprabowati; Hartuti Purnaweni (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Society is an entity where every human individual tries to adapt and blend with his environment so as to form a mutually reinforcing social bond. Social ties in society create a culture that is manifested in everyday life in the form of norm, customs and traditions. Cultural traditions have a dynamic value that evolves in tandem with the evolution of the era. Cultural traditions are no longer just symbols to be understood symbolically, they also contain values that indicate ecological values (on a local spectrum), as well as prospective commercial values. Nyadran Gebyog tradition in Pungangan Village is an affirmation of the people's identity, as it is a reflection of the community's appreciation of the natural environment for the sufficiency provided by nature over the years for the community's basic needs, as well as a capital for economic development through the concept of ecotourism. Ecotourism development that is in accordance with the socio-cultural pulse of the community will produce a good synergy between the elements of the natural and socio-cultural environments, resulting in a higher level of public acceptance of the ecotourism idea.Keywords: Ecotourism, socio-culture, Nyadran Gebyog, Pungangan Village.